Better Cognitive Function Increase the Independence Level of Eldery - Syahreza Nazhara; Maria Regina Rachmawati (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Background: The number of elderly is increasing, estimated by the year of 2020 reach 28,800,000 (11.34%) ofthe total population. One of the common problems of the elderly is dependence on daily activity function andcognitive function. There is no data about the relationship between cognitive function with independence indaily activity in rthe nursing home. The objective of this study is to analyze the relationship between cognitivefunction with the level of independence on daily activity in the elderly who live in a nursing home.Methods: Study design was analytical observation by the cross-sectional study. The instruments that used inthis study was the Mini Mental Status Evaluation (MMSE) questionnaire, to measure the cognitive function,Katz index questionnaire to measure the level of independency. analyzed by Spearman correlation test.Results: The subjects were 107 elderly, the mean age was 69.7±8.7. MMSE score were 0-17 (severe), 18-23(moderate), and 24-30 (Normal), respectively were; 62 (57.9%) ,26 (24.3%),19 (17.8%). Katz Index score were02 (severe dependency), 3-5 (moderate dependency), and 6 (independence), respectively were; 8 (7,5%), 24(22,4%), 70 (70,1%). There is the positive relationship between cognitive function and the level of independencein elderly (p=0.000, r = 0.335).Conclusion: The higher cognitive function correlates with the higher independence level of elderly in nurseryhome.Keywords: cognitive function, independence level, elderly, nursery home